Smart Office Document Management System With Descriptive Analytics and SMS Alerts - Rose Mae U. Reyes, Joana; V. Origines Jr, Domingo (LPPM Universitas Duta Bangsa Surakarta, 2024)
This study aimed to address the inefficiencies of manual document submission and deliver a user-friendly dashboard that presents submitted document data through various visualizations and data analytics. The approach enhances decision-making processes, operational efficiency, communication, and collaboration within organizations. Descriptive data analytics methodology was employed to effectively summarize and present key data points. The project also adopted the Rapid Application Development methodology during its development. As a result, the project received favorable evaluations from its assessors, achieving high overall mean scores of 4.17 for functionality, 3.95 for reliability, and 3.98 for usability. Consequently, by integrating descriptive data analytics and SMS notification system, the implementation notably benefited the Human Resource Management Office of Davao del Sur State College by providing a Web System with dashboard equipped with visualizations such as count metrics, bar graphs, and tables. Additionally, the system facilitated seamless information updates, empowering administrators to make evidence-based decisions and identify trends within their data.